Batu Tahu As A Form Of Conservation Of Coastal Areas And Habitat Of Biological Resources In Bengkulu From A Legal Perspective - Rizky Juventus Simangunsong; Intan Riwayaty Amran (Fakultas Hukum Dehasen, 2024)
Batu Tahu is one of the icons of coastal tourism in Bengkulu City. This beach is unique in the form of coral rock formations that form beautiful cliffs along the coastline. Apart from its natural beauty, Batu Tahun Beach is also a habitat for various types of marine biological resources, such as coral reefs, fish, and other biota. This research aims to examine the conservation efforts carried out in the Batu Tahu Beach area in order to preserve the coastal area and protect the biological resource habitat within it. Using a qualitative descriptive approach, this study analyzes the conservation practices implemented, such as limiting tourist activities, protecting coral reef ecosystems, and educating visitors about the importance of preserving the coastal environment. Data was obtained through field observations, interviews with managers, and study of related literature. It is hoped that the results of the research will provide an overview of conservation efforts in the coastal tourist area of Bengkulu City and become a reference for the management and preservation of biological resources in similar areas.